2018
DOI: 10.1093/jpids/piy044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Previous Antibiotic Use as a Risk Factor for Acute Gastroenteritis Among Children in Davidson County, Tennessee, 2014–2015

Abstract: Previous antibiotic use among children was associated with increased odds of AGE, irrespective of etiology, and this association was stronger with more recent antibiotic use. Previous antibiotic use was associated also with more severe AGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…The highest infection rates (89.47%) were noticed in age group (1-12 months) followed by 3 (7.90%) within the age group (13-24 months). The statistical analysis showed highly significant differences among gender and age as shown in Figure (2) and Table (4). Distribution of Cryptosporidium spp.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The highest infection rates (89.47%) were noticed in age group (1-12 months) followed by 3 (7.90%) within the age group (13-24 months). The statistical analysis showed highly significant differences among gender and age as shown in Figure (2) and Table (4). Distribution of Cryptosporidium spp.…”
Section: Resultsmentioning
confidence: 91%
“…The rate of human astrovirus infection among males 9(64.29%) was higher than females 5(35.71%) and statistically significant. The age of patient ranged from 1month to 60 months, the positive result 11(78.57%)was in the age group 1-12 month and 3 (21.43%) their age was 13-24months, while no positive cases among other age groups, statistical analysis showed highly significant differences as shown in Figure (1) and Table (2). Patients with gastroenteritis were divided into three groups according to the various types of feeding, the highest infection rate of human astrovirus was noticed in patients who used artificial feeding 13(92.86%) followed by breastfeeding 1(7.14%), while there were no positive cases in children with mixed feeding.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Any recent exposure to antibiotics might influence the susceptibility of the host to AGE and its complications. An epidemiological study conducted at a single regional centre reported that recent antibiotic therapy in children increased the probability and severity of AGE [ 9 ]. However, this study may have been biased due to the small study population and inaccurate history of antibiotic use.…”
Section: Introductionmentioning
confidence: 99%
“…Entre essas causas bacterianas graves, Salmonella não tifoide e Campylobacter sp são as causas mais comuns nos Estados Unidos. A taxa de incidência por 100.000 pessoas em 2016 foi estimada pelo programa de vigilância ativa controlada pelo Centers for Disease Control and Prevention, Food Net, com resultados como segue: Salmonella (15.4%),Campylobacter (11.8%), Shigella (4.6%), E. coli (2.8%), Vibrio (0.45%) 9 . A diarreia infecciosa está entre as principais causas de doença em todo o mundo e está associada a 1,5 a 2,5 milhões de mortes por ano 10 .…”
Section: Introductionunclassified